Decellularized Cartilage Matrix as a Novel Biomatrix for Cartilage Tissue-Engineering Applications - Silke, Schwarz; Körber, Ludwig; Elsässer, Alexander; Goldberg-Bockhorn, Eva; Seitz, Andreas M.; Duerselen, Lutz; Ignatius, Anita; Walther, Paul; Breiter, Roman; Rotter, Nicole (Tissue Engineering: Parts A, B, and C, 2012)
Damage of cartilage structures in the head and neck region as well as in orthopedic sites are frequently caused by trauma, tumor resection, or congenital defects. Despite a high demand in many clinical fields, until today, no adequate cartilage replacement matrix is available for these fields of application. Materials that are clinically applied for joint cartilage repair still need optimization due to difficult intraoperative handling and risk of early mechanical damage. We have developed and applied a novel chemical process to completely decellularize and sterilize human and porcine cartilage tissues (meniscus cartilage and nasal septum) to generate a new type of bioimplant matrix. To characterize this matrix and to determine the effect of the decellularization process, the content of denatured collagen (w(D)) and the content of glycosaminoglycans (GAGs) (w(G)) were determined. Possible cytotoxic effects and cellular compatibility of the matrix in vitro have been examined by seeding processed cartilage biomatrices with human primary chondrocytes as well as murine fibroblasts (L929). Vitality and state of metabolism of cells were measured using MTS assays. Both cell types adhered to scaffold surfaces and proliferated. No areas of growth inhibition or cytotoxic effects were detected. New synthesis of cartilage-specific extracellular matrix was observed. By histological staining, electron microscopy, and mu CT analysis, an increase of matrix porosity, complete cell elimination, and high GAG removal were demonstrated. Being from natural-origin, processed xenogenic and allogeneic cartilage biomatrices are highly versatile with regard to shape, size, and biomechanics, making them promising candidates for various biomedical applications.